2014
DOI: 10.3923/ijbc.2015.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Supplementation of Fenugreek (Trigonella foenum-graecum L.) on Serum Biochemical Parameters of Rats Fed High Cholesterol Diet

Abstract: Thirty-two rats were divided into four groups (8 rats/each) named as 1, 2, 3 and 4. Group 1 kept on basal diet and served as a control group. Whereas, group 2 kept on the basal diet mixed with 1% cholesterol (high cholesterol diet). Groups 3 and 4 kept on the high cholesterol diet mixed with Fenugreek seed powder 5 and 10%, respectively. Total cholesterol, low-density lipoprotein cholesterol (LDL-c) and alanine transaminase (ALT) activity were significantly increased (32.4±0.2; 12.2±1.5 mg dLG 1 ; 26.5±0.6 IU … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…These results are similar to those reported by Elmahdi and El-Bahr (2015) who reported that dietary supplementation with 5 or 10% Trigonella foenum graecum to rats fed high cholesterol diet did not show any significant effect on serum total protein and albumin. Khalil (2004) reported that non diabetic rats treated with fenugreek recorded nonsignificant increase in serum total protein, albumin and globulin compared with the control ones.…”
Section: Serum Total Protein and Albuminsupporting
confidence: 92%
“…These results are similar to those reported by Elmahdi and El-Bahr (2015) who reported that dietary supplementation with 5 or 10% Trigonella foenum graecum to rats fed high cholesterol diet did not show any significant effect on serum total protein and albumin. Khalil (2004) reported that non diabetic rats treated with fenugreek recorded nonsignificant increase in serum total protein, albumin and globulin compared with the control ones.…”
Section: Serum Total Protein and Albuminsupporting
confidence: 92%
“…The present study shows that fenugreek as growth promoter and has many therapeutic properties in animal's metabolism and physiology [118], [119]. It reduces plasma cholesterol levels [120], enhances food consumption, indicates a stimulatory influence on immune functions [121], decreases kidney/body weight ratio [122], blood glucose [116], blood lipid levels and improves hemorheological parameters. Since the systemic studies on the effect of fenugreek on heart are very limited as only on the in vivo, the study on in vitro aimed to investigate the mechanistic action of fenugreek as therapeutic cardioprotectant agents suitable as a daily food supplement against ischemic heart injury.…”
Section: Fenugreek the Notorious Ancient Medicine As Herb And Spicementioning
confidence: 74%
“…Additionally, fenugreek can reduce blood sugar and cholesterol levels in diabetic patients. A low dose of fenugreek (less than 5%) improves the rats' liver function [120]. Fenugreek contains a healthy polysaccharide that triggers the breakdown of fat and sugar metabolism in the body.…”
Section: Therapeutic Uses Of Fenugreekmentioning
confidence: 99%
See 1 more Smart Citation